Triadin Decrease Impairs the Expression of E-C Coupling Related Proteins in Muscles of MPTP-Induced Parkinson’s Disease Mice - Seo, Min Hyung; Yeo, Sujung (Frontiers in Neuroscience, 2021)
Parkinson’s disease (PD), caused by destruction of dopaminergic neurons in the brain, leads to motor symptoms like bradykinesia, tremor, and walking impairments. While most research effort focuses on changes in neuronal pathology we examined how muscle proteins were altered in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD. A Ca2+ release channel complex, consisting of ryanodine receptors (RYR), triadin, and calsequestrin, is important for excitation-contraction coupling in the sarcoplasmic reticulum membrane in muscles. Thus, we investigated changes in the RYR Ca2+ release channel components in PD mice model. Based on a report that triadin deletion impairs skeletal muscle function, we also investigated how the knock-down of triadin affects other components of the RYR channel in the PD model. In this study, the expression levels of the components of RYR channels decreased in the quadriceps femoris muscle of MPTP-induced PD mice and in C2C12 cells treated with 1-methyl-4-phenylpyridinium. We show that decreased triadin levels decrease RYR and calsequestrin levels. These results suggest that the levels of proteins related to Ca2+ channel function decreased in this model, which could impair muscle function. We conclude that muscle function alterations could add to the bradykinesia and tremor in this model of PD.